KONFLIK SOSIAL DALAM NOVELET AL BAHRI PADA KUMPULAN NOVELET TIGA OMBAK KARYA GOLA GONG: TINJAUAN SOSIOLOGI KARYA SASTRA DAN IMPLIKASINYA TERHADAP PEMBELAJARAN DI SMA - dan Vita Ika Sari, Larasaji Narindri Arumda, Leli Triana, (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Pancasakti Tegal, 2021)
This research discusses the social conflict in Al Bahri novelet in the collection of novelets Tiga Ombak by Gola Gong by reviewing it according to the sociology of literature with qualitative research methods. The purpose of this study is to describe the social conflict in Al Bahri's novelette in the collection of novelets Tiga Ombak by Gola Gong and the implications of the research results on Indonesian language learning in high school. Based on the results of the study, it can be found that social conflicts in the novelet collection consist of social conflicts within individuals 51%, social conflicts between groups and individuals 24%, social conflicts between individuals and individuals 20%, and social conflicts between groups 5% and can be implied on Indonesian language learning in SMA class XII at KD 3.9 analyzes the content and language of the novel.